The call of the whole in understanding the development of sustainable ventures - Muñoz, Pablo; Dimov, Dimo (Journal of Business Venturing, 2015)
This paper examines the development process of sustainable ventures by focusing on three substantive markers, namely the ideas, actions, and exchange relationships articulated and instigated by the entrepreneurs in question. Based on data from 45 sustainability-oriented new ventures, it examines the causal configurations behind the manifestations of these markers using Fuzzy-Set Qualitative Comparison Analysis (fsQCA). The analysis also reveals two distinct opportunity development paths. The first, conformist, operates in an enabling supporting context as sustainability conveyor. The second, insurgent, path operates as a change agent against an establishment that is not conducive to sustainability ideals.